Correlation between serum level of cortisol, interleukin-10 and degree of adhesion after laparotomy and laparoscopy in rabbit with abrasion model - Ridwan Mataram (RSUP Dr. Kariadi, 2016)
Background : Intraperitoneal adhesions after abdominal and pelvic surgery procedures occurred almost in 95% of cases. This research will prove the relationship between serum levels of cortisol in response to stress with increased levels of IL-10 and the degree of adhesion after laparotomy and laparoscopy Methods : This study is an experimental laboratory, with a posttest design approach using 12 New Zealand rabbits after adaptation for 1 week were divided into 2 groups. The first group ( K1) was performed laparotomy with abration the ilium , group-2 ( K2) was performed laparoscopy with abration the ilium too. All groups taken its blood sample before and 6 hours after operation to be assessed levels of cortisol with ELISA kit. 6 days after operation (day of 7th) , all group determinate and performed laparotomy, than assessed the degree of adhesion and the level of IL-10 from its peritoneal fluid. Statistical tests were used to assess defferences in the level of cortisol, IL-10 and degree do adhesion between laparotomy and laparoscopy. Data analysis was done using SPSS. Results : There was significant difference in the level of cortisol, IL-10 and degree of adhesion among groups ( p = 0.021, p < 0.001, p = 0.002 ). There were negatif correlation ( high ) between the level of blood cortisol with IL-10 ( r = - 0.805, p = 0.0 ) and significant negative correlation between the level of IL-10 with the degree of adhesion ( r = -0,833, p = 0.001 ). Conclusion : Laparoscopic surgery can minimize the effects of systemic stress and immune response, so as to lower the incidence of adhesion